Characterization of Dietary Constituents, Phytochemicals, and Antioxidant Capacity of Carpobrotus edulis Fruit: Potential Application in Nutrition - Carlota R. Marques; Carla Sousa; Carla Moutinho; Carla Matos; Ana Ferreira Vinha (Applied Sciences)
Carpobrotus edulis (chorão-da-praia) is an edible and medicinal plant native to South Africa, currently distributed worldwide. Due to the urge for novel foods, invasive species can be considered valuable food supplies to accomplish the current goals of the 2030 Agenda. In this study, C. edulis fruits harvested in northern Portugal’s Atlantic coast were evaluated for proximate analysis (AOAC methods), mineral contents (ICP-MS), and fatty acid composition (GC-FID). Total phenolics, flavonoids, and antioxidant activity (DPPH and FRAP assays) were carried out by colorimetric methods. The fruits exhibited high amounts of carbohydrates (60.5%), ash (10.9%), and total crude protein (22.8%). A low content of total fat (4.5%) was observed. Linoleic acid (C18:2n6c) was the predominant unsaturated fatty acid (52.08%) among the 11 identified fatty acids. The highest amounts of total phenolics (311.7 mg GAE/g) and flavonoid (50.43 mg CE/g) contents were observed in hydroalcoholic fruit extracts. The high concentration of bioactive compounds in the C. edulis fig is directly reflected in its antioxidant properties, enhancing the usefulness of this invasive species in food and pharmaceutical industries.